Renewal of Islamic Law: Comparative Study between Progressive Islamic Theory and Ijtihad Method - Isnain La Harisi; Deni Irawan; M. Wahid Abdullah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This study compares the theory of progressive Islam and the ijtihad method in the context of Islamic legal reform. Using a qualitative approach through literature review, this research evaluates the characteristics, strengths, and weaknesses of both approaches. The analysis reveals that progressive Islam is often seen as innovative in addressing contemporary challenges, offering more flexible responses. However, this approach may risk overlooking the foundational principles of established Sharia. Conversely, the ijtihad method, which is part of the science of ushul fiqh, provides a more structured framework for interpreting laws from religious texts. Through ijtihad, Islamic law is expected to evolve continuously, avoiding stagnation without overstepping Sharia boundaries. The critical analysis shows that the ijtihad method holds greater potential to produce sustainable legal reforms that align with Sharia principles, compared to progressive Islam, which relies more on liberal interpretation of religious texts. This study concludes that the ijtihad method offers flexible legal reform while maintaining consistency with the core values of Islam.